Inisiatif Lingkungan Berbasis Keagamaan dalam Memerangi Green Financial Crime: Konsep Kesakralan dan Pengelolaan - Thoriquttyas, Titis; Rohmawati, Nita (Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK), 2024)
Green financial crime seriously threatens the sustainability of the environment and the integrity of the global economy. This study aims to investigate the role of environmental initiatives to religious foundations with a religious foundation in countering green financial crime by reviewing relevant literature, examining religious teachings on environmental stewardship, and evaluating the influence of religious advocacy on public policy and community behavior. In the practical sense in the Indonesian context, Muhammadiyah's humanitarian arm has been involved in disaster relief, focusing on environmental sustainability in recovery efforts. This includes advocating for better waste management and building resilient, eco-friendly infrastructure in disaster-prone areas. These initiatives highlight how organizations use their religious influence, aligning faith-based teachings with practical efforts. Thematic analysis is used in this study to find and examine themes and patterns in the data gathered. The results of this study show that faith-based activities play a significant role in the local and global fight against green financial crime. It is essential for religious organizations to prioritize environmental awareness because of the pressing nature of environmental crises and the significant moral, ethical, and practical effect that religion has. The integration of religious ideas and the utilization of religion-based organizations' strengths can significantly augment efforts aimed at combating green financial crime, thereby resulting in more equitable and sustainable outcomes for both society and the environment.